2000
DOI: 10.2466/pr0.87.7.1139-1146
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Texts With Word-Processing

Abstract: The aim of the research was to study the use of a word processor to improve writing and revising skill by 28 pairs of primary school children. Analysis confirmed greater difficulty in the drafting of texts than with traditional handwriting, but the increase in the number of words and errors does not imply improvement in lexical and orthographical aspects. The guided revision of texts on a word processor may support beginning writers' expression and, with increasing ease, allow them to use greater precision in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The availability of digital sources often makes drafting a fi rst version of a text easier, although Nuvoli (2000) showed that primary school students had more diffi culty in drafting with the computer than with pen and paper. Copying and pasting (from) sources might facilitate the production of texts but requires, at the same time, more effort and higher abilities to check coherence of ideas in the text in the revision phase ( Oliver, 2004 ).…”
Section: Changing Concepts Of Writingmentioning
confidence: 99%
“…The availability of digital sources often makes drafting a fi rst version of a text easier, although Nuvoli (2000) showed that primary school students had more diffi culty in drafting with the computer than with pen and paper. Copying and pasting (from) sources might facilitate the production of texts but requires, at the same time, more effort and higher abilities to check coherence of ideas in the text in the revision phase ( Oliver, 2004 ).…”
Section: Changing Concepts Of Writingmentioning
confidence: 99%
“…Our review of the literature suggested that one area where the response format (i.e., computer entry of responses versus handwritten) might be expected to result in differences was in the essay length. Studies on the effects of word processors on writing, for example, have shown that computers can result in longer written responses (Handley-More, Deitz, Billingsley, & Coggins, 2003;Nuvoli, 2000;Peterson, 1993;Li Nim-Yu, 1990). One-way GLM ANOVAs, however, did not indicate significant differences in word counts for either notes (F(1, 209) D 1.262, p D .262) or essays (F(1, 209) D .111, p D .740) between Study 1 and Study 2.…”
Section: Exploring the Influence Of Stance And Node Sizementioning
confidence: 99%
“…Some research has shown that word processing can remove some of the difficulties young children encounter when they write by hand (Chang & Osguthorpe, 1990). On the other hand, Nuvoli's (2000) research into the use of a word processor to improve primary children's writing and revising found that children had greater difficulty drafting their texts with computers than with handwriting. Computer programs that provide prompts assist young writers in being more strategic (Cochran-Smith, 1991;Daiute, 1986;Jones, 1994).…”
Section: Technology and Writingmentioning
confidence: 99%